Numerical Simulation of Propagation of Unsteady Tribrachial Flames in Laminar Non-Premixed Jets (Journal of Informatics and Mathematical Sciences, 2018)
The characteristics of propagating Tribrachial Flames in non-premixed laminar jets have been investigated computationally, using a two dimensional model in ANSYS FLUENT 16.0. The edge of the propagating flame in a laminar jet regime has a Tribrachial flame structure: a lean premixed flame, a rich premixed flame, and a diffusion flame, all extending from a single location. This is usually observed in non-premixed combustion such occurring in burners. Such flames are important in the interaction of heat and mass transfer with chemical reactions in gas turbines and commercial burners. A computational study has been performed to assess the laminar tribrachial flame propagation in methane jets and to compare the tribrachial flame propagation for various flow rates. With an increase in the fuel jet Reynolds number, the tribrachial point is found to move closer to the nozzle. Additionally the tribrachial point is found to become larger with an increase in the Reynolds number.
Keywords: Combustion; Numerical simulation; Tribrachial flame; Laminar flame; Flame propagation